Needs For Love And Belongingness In The Character Of HuckFinn In Mark Twain's The Adventures Of Huckleberry Finn Novel:A Humanistic Psychological Approach - Pratama, Febri Rizqi; , Drs. Abdillah Nugroho, M. Hum; , Drs. Sigit Haryanto, M.Hum (2014)
The major problem of this study is to reveal how the needs for love and belongingness reflected in The Adventure of Huckleberry Finn novel by Mark Twain. The objectives of the study are to analyze the novel based on its structural elements and on the humanistic psychology analysis. In analyzing the novel, the researcher uses qualitative study. There are two kinds of data source, namely primary and secondary data source. The primary data is the novel of The Adventure of Huckleberry Finn, while the secondary data is any literature related with this study. The researcher collects the data from both primary and secondary data sources by using library research. The technique of data analysis is descriptive technique. The result of the research shows that: First, structural elements of The Adventure of The Huckleberry Finn novel builds good unity. Second, The Adventure of Huckleberry Finn describes the needs for love and belongingness of Huck Finn as major character. Third, Huck Finn is orphan, but he needs attention from another people around him.